Nitric oxide and oxidative stress is associated with severity of diabetic retinopathy and retinal structural alterations - Sharma, Shashi; Saxena, Sandeep; Srivastav, Khushboo; Shukla, Rajendra K; Mishra, Nibha; Meyer, Carsten H; Kruzliak, Peter; Khanna, Vinay K (Clinical & experimental ophthalmology, 2015)
BACKGROUND: The aim of the study was to determine plasma nitric oxide (NO) and lipid peroxide (LPO) levels in diabetic retinopathy and its association with severity of disease. DESIGN: Prospective observational study. PARTICIPANTS: A total of 60 consecutive cases and 20 healthy controls were included. METHODS: Severity of retinopathy was graded according to early treatment diabetic retinopathy study (ETDRS) classification. Photoreceptor inner segment ellipsoid band (ISel) disruption and retinal pigment epithelium (RPE) alteration were graded using spectral domain optical coherence tomography. Data were statistically analyzed. MAIN OUTCOME MEASURES: Plasma thiobarbituric acid reactive substances, NO assay and reduced glutathione (GSH) were measured using standard protocol. RESULTS: Increased severity of diabetic retinopathy was significantly associated with increase in plasma levels of LPO (P < 0.05), NO (P < 0.001) and decrease in plasma levels of GSH (P < 0.0001), ISel disruption (P < 0.001) and RPE topographic alteration (P < 0.01). CONCLUSION: Increased plasma NO levels are associated with increased severity of diabetic retinopathy. For the first time, it has been demonstrated that increased plasma LPO, NO and decreased GSH levels are associated with in vivo structural changes in inner segment ellipsoid and RPE.
Keywords: nitric oxide; retinální pigmentový epitel; optická koherentní tomografie; oxidative stress; peroxidace lipidů; Aged; Oxidative Stress; Retinal Photoreceptor Cell Inner Segment; Aged, 80 and over; stupeň závažnosti nemoci; lidé středního věku; senioři; Severity of Illness Index; spectral domain optical coherence tomography; lidé; Adult; Thiobarbituric Acid Reactive Substances; Middle Aged; Prospective Studies; dospělí; Lipid Peroxides; Diabetes Mellitus, Type 2; prospektivní studie; diabetic retinopathy; nitrosative stress; Tomography, Optical Coherence; diabetes mellitus 2. typu; Female; glutathion; Nitric Oxide; diabetická retinopatie; senioři nad 80 let; Lipid Peroxidation; Male; ženské pohlaví; Humans; oxidační stres; mužské pohlaví; látky reagující s kyselinou thiobarbiturovou; oxid dusnatý; lipidové peroxidy; Retinal Pigment Epithelium; Diabetic Retinopathy; Glutathione; vnitřní segment fotoreceptoru sítnice